Impact of statin therapy on glycemic status in diabetes-naïve patients: a systematic review - Arora, Sonia; Kohli, Poonam Gakhar (International Journal of Research in Medical Sciences, 2026)
While statins are widely prescribed for the primary prevention of cardiovascular disease, recent evidence suggests that they may influence glucose regulation and contribute to the development of new-onset diabetes mellitus (NODM) in individuals without pre-existing diabetes. This systematic review evaluates the impact of statin therapy on glycemic parameters in diabetes-naïve adults. Electronic databases were searched for studies assessing the effects of statins on fasting plasma glucose (FPG), HbA1c, insulin sensitivity and NODM, including randomized controlled trials, cohort studies and case–control studies. A qualitative synthesis was performed and results were summarized in tables. Fifteen studies involving more than 600,000 participants were included. Statin therapy was associated with increases in FPG ranging from 3 to 12 mg/dl and HbA1c from 0.1 to 0.4%. A higher risk of NODM was observed with high-dose and prolonged statin use. Findings regarding insulin sensitivity and β-cell function were variable and certain statins such as pitavastatin demonstrated a more favorable glycemic profile. Although a small deterioration in glycemic control was noted, the absolute risk of diabetes remained low. Overall, statin therapy in diabetes-naïve patients is associated with modest worsening of glycemic indices and a slight increase in NODM risk, particularly with high-intensity regimens or in individuals with baseline metabolic risk factors; however, the cardiovascular benefits of statins outweigh these potential glycemic effects, supporting their continued use with appropriate monitoring and individualized risk assessment.